ANALYSIS OF DIFFERENCES IN TRANSFORMATIONAL LEADERSHIP BETWEEN GENERATIONS X AND Y AND THE EFFECT ON POWER PLANT COMPANY PERFORMANCE - Azam Firman Syatoto, Ilma (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2021)
This study analyzes the differences in transformational leadership between generation X and generation Y and its effect on company performance in two power generation companies in North Sumatra Province. The number of samples was 50 people in each group of generations X and Y. Data analysis using SPSS included F-test, T-test, the coefficient of determination, and independent sample T-test. The F-test shows that charismatic variables, inspirational motivation, intellectual stimulation, and individual considerations simultaneously affect the performance of each group of generation X and generation Y. The results of the T-test in generation X show that the variables of inspirational motivation and individual considerations are partially has a positive and significant effect on company performance, meanwhile in generation Y only charismatic variables have a positive and significant influence on company performance. The results of the coefficient of determination said that the transformational leadership of generation X contributed 70.2% to the company performance, while the transformational leadership of the Y generation contributed 22.3% to the company performance. Independent sample T-test said that there was a significant difference between the transformational leadership of the generation X and generation Y.